Chronic Hypopituitarism Associated with Increased Postconcussive Symptoms Is Prevalent after Blast-Induced Mild Traumatic Brain Injury - Undurti, Arundhati; Colasurdo, Elizabeth A.; Sikkema, Carl L.; Schultz, Jaclyn S.; Peskind, Elaine R.; Pagulayan, Kathleen F.; Wilkinson, Charles W. (Frontiers in Neurology, 2018)
The most frequent injury sustained by U.S. service members deployed to Iraq or Afghanistan is mild traumatic brain injury (mTBI), or concussion, by far most often caused by blast waves from improvised explosive devices or other explosive ordnance. TBI from all causes gives rise to chronic neuroendocrine disorders with an estimated prevalence of 25-50%. The current study expands upon our earlier finding that chronic pituitary gland dysfunction occurs with a similarly high frequency after blast-related concussions. We measured circulating hormone levels and accessed demographic and testing data from two groups of male veterans with hazardous duty experience in Iraq or Afghanistan. Veterans in the mTBI group had experienced one or more blast-related concussions. Members of the deployment control (DC) group encountered similar deployment conditions but had no history of blast-related mTBI. Twelve of 39 (31%) of the mTBI participants and three of 20 (15%) veterans in the DC group screened positive for one or more neuroendocrine disorders. Positive screens for growth hormone deficiency (GHD) occurred most often. Analysis of responses on self-report questionnaires revealed main effects of both mTBI and hypopituitarism on postconcussive and PTSD symptoms. Symptoms associated with pituitary dysfunction overlap considerably with those of PTSD. They include cognitive deficiencies, mood and anxiety disorders, sleep problems, diminished quality of life, deleterious changes in metabolism and body composition, and increased cardiovascular mortality. When such symptoms are due to hypopituitarism, they may be alleviated by hormone replacement. These findings suggest consideration of routine post-deployment neuroendocrine screening of service members and veterans who have experienced blast-related mTBI and are reporting post-concussive symptoms.